Preservice Science Teachers as Mediators of Indigenous Artisanal Knowledge: A Community-Based Ethnoscience Project in Central Lombok - Bayani, Faizul; Hulyadi, Hulyadi; Pomeistia, Meilynda; Sudirman, Sudirman; Rahman, Rahman; Hidayah, Thauhidayatul; Hardianti, Dina; Safitri, Temi Ainul; Gargazi, Gargazi (LITPAM, 2025)
This qualitative single-case ethnoscience study explored how preservice science teachers reconstructed indigenous knowledge from local artisanal practices into potential school science learning resources. Conducted in an Ethnoscience course in the Science Education Study Program at Universitas Qamarul Huda Badaruddin Bagu, Central Lombok, the project adopted an ethnoscience-oriented project-based practicum (EthnoPjBL) in which one intact class collaborated with artisans involved in knife forging, clay brick and roof-tile production, herbal medicine and jamu kunyit asam preparation, palm-sugar and sweet tuak processing, and plastic and bamboo weaving. Data from participant observation, field notes, interviews, structured analysis tables, student scientific report drafts, concept maps, reflective worksheets, and course documents were analysed through thematic coding, constant comparison, and concept map interpretation. The findings show that preservice teachers identified dense clusters of phenomena, for example heat transfer, phase change, mixtures, plant physiology, microbial processes, and structural mechanics, mapped these onto canonical concepts and junior and senior secondary curriculum topics, and produced curriculum-linked representations that support contextualised and integrated science learning while developing epistemological awareness, ethical sensitivity, and capacity to pedagogically mobilise indigenous knowledge.